Tradition Of Cleaning For Reacting Social, Religion And Environment Education - Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Rimun Wibowo; Zulkifli Rangkuti; Zakky Muhammad Noor (Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to investigate the tradition of cleaning value for education. The research method uses an ethnographic qualitative approach. This method is implied because this research is related to society and culture as well as the tradition of community. To gather data was used as an in-depth interview. Sample are selected through purposive technique. The result is probed meticulously through triangulation technique and triangulation sources. The result shows the societies still preserve tradition cleaning to tighten social connection and save the societies from an ailment which is impacted by poor hygiene as well as avoiding from a natural disaster. Another is societies make garbage bank as the method to reduce an-organic sewage and decline organic garbage because the societies bury organic sewage in biopori hole. As a result, It can combat nature disaster. The other is there is social education because the tradition as exemplary to young generation to continue this habit in the future and as a model to build social solidarity among societies. It also has environmental education because the societies have to learn to care about nature environment and religion value because religion teaches the societies to perform hygiene in environment, body, house and the place for worship